Pump it up: making single-pit emptying safer in rural Bangladesh - Balasubramanya, Soumya; Evans, B.; Ahmed, R.; Habib, A.; Asad, N.S.M.; Vuong, L.; Rahman, M.; Hasan, M.; Dey, D.; Camargo Valero, M.A. (IWA Publishing, 2016)
Safe emptying and disposal of fecal sludge from pit latrines in rural areas has become a priority for the Government of Bangladesh. In this paper, we calculate the volume and characterize the hazards of managing sludge to identify technologies for safely emptying rural single pits. In Bhaluka subdistrict, an estimated 15,000 m3 of sludge is produced annually. Physical, chemical, and microbial analysis of samples of sludge taken from pit latrines indicate that the sludge has a high moisture content of around 90%, a C:N ration of 10:1, and a helminth presence of 41 eggs/g. In a field test of alternative emptying technologies, simple pumps such as the gulper emerged as feasible for use in rural areas, due to the liquid nature of the sludge, narrow roads, and limited incomes of rural households. The results suggest that current practices of emptying liquid sludge manually without any protective equipment poses risks to those who handle sludge, and the process needs to be semi-mechanized with immediate effect. These results are being used by the Bangladesh government to design policy for sludge management. In the near future, an organized service that safely empties single pits and transports sludge for treatment needs to be urgently designed.